Do‐Not‐Attempt‐Resuscitation orders for people with intellectual disabilities: dilemmas and uncertainties for ID physicians and trainees. The importance of the deliberation process. Issue 3 (26th August 2016) - Wagemans, A. M. A.; van Schrojenstein Lantman‐de Valk, H. M. J.; Proot, I. M.; Bressers, A. M.; Metsemakers, J.; Tuffrey‐Wijne, I.; Groot, M.; Curfs, L. M. G.
Abstract: Background: Not much is known about Do‐Not‐Attempt‐Resuscitation (DNAR) decision‐making for people with intellectual disabilities (IDs). The aim of this study was to clarify the problems and pitfalls of non‐emergency DNAR decision‐making for people with IDs, from the perspective of ID physicians. Methods: This qualitative study was based on semi‐structured individual interviews, focus group interviews and an expert meeting, all recorded digitally and transcribed verbatim. Forty ID physicians and trainees were interviewed about problems, pitfalls and dilemmas of DNAR decision‐making for people with IDs in the Netherlands. Data were analysed using Grounded Theory procedures. Results: The core category identified was 'Patient‐related considerations when issuing DNAR orders'. Within this category, medical considerations were the main contributory factor for the ID physicians. Evaluation of quality of life was left to the relatives and was sometimes a cause of conflicts between physicians and relatives. The category of 'The decision‐maker role' was as important as that of 'The decision procedure in an organisational context'. The procedure of issuing a non‐emergency DNAR order and the embedding of this procedure in the health care organisation were important for the ID physicians. Conclusion: The theory we developed clarifies that DNAR decision‐making for people with IDs is complex and causes uncertainties. This theory offers a sound basis for training courses for physicians to deal with uncertainties regarding DNAR decision‐making, as well as a method for advance care planning. Health care organisations are strongly advised to implement a procedure regarding DNAR decision‐making.